Low-heat early-strength steel fiber mass concrete and preparation process thereof
By adding steel fibers to large volume concrete and controlling the casting temperature, the problems of low early strength and excessive hydration heat of large volume concrete are solved, and the effects of high early strength and low hydration heat are achieved, which improves the compressive and crack resistance of concrete.
Patent Information
- Application Number
- CN202411571550.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-06
AI Technical Summary
During the pouring process, large internal and external temperature differences are large due to hydration heat, and the early strength is low and prone to cracking. The hydration heat will also lead to the decomposition of ettringite, affecting the strength and structural stability of the concrete.
The low-heat early strength steel fiber large volume concrete and its preparation process are adopted. By uniformly adding cement, mineral blends, fine aggregates, coarse aggregates and steel fibers to the forced mixer, and controlling the casting temperature, reducing the heat of hydration and improving early strength.
It effectively reduces the hydration heat of large-volume concrete, reduces the temperature difference between inside and outside, improves early strength, enhances compressive strength and crack resistance, and extends the service life of concrete.
Smart Images

Figure BDA0005120585130000031 
Figure BDA0005120585130000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a low-heat early-strength steel fiber mass concrete and a preparation process thereof. Background Art
[0002] In recent years, with the continuous increase in the scale of projects, reinforced concrete structures need to withstand greater loads, which puts higher requirements on the strength and durability of concrete. The temperature crack control and strength growth requirements brought about by mass concrete pouring have become important factors affecting project safety. Large hydration heat is generated inside the mass concrete, forming a large temperature difference between the inside and outside. The early strength of the concrete material is low and is not enough to withstand stress and cracking occurs. Performance degradation is bound to occur in the later stage, and even other engineering disasters may be induced in severe cases. Not only that, the hydration heat of mass concrete will also cause the internal calcium sulfonate to decompose. When the temperature drops, the calcium sulfonate will regenerate, causing the expansion of the mass concrete to be destroyed, thereby causing the mass concrete structure to be destroyed, thus affecting the strength of the mass concrete.
[0003] In response to the above problems, the present invention discloses a low-heat early-strength steel fiber mass concrete and its preparation process, which reduces the temperature difference between the inside and outside of the mass casting structure by reducing the hydration heat, while increasing the early strength to cope with temperature stress and other loads, thereby solving the problem of easy cracking of mass casting structures in major projects, and has important application value in the field of building materials technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a low-heat early-strength steel fiber mass concrete and a preparation process thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A preparation process of low-heat early-strength steel fiber mass concrete comprises the following steps:
[0007] Evenly add cement, mineral admixture, fine aggregate, coarse aggregate and steel fiber into a forced mixer, stir for 10-30 seconds to make the materials evenly mixed, then inject water, continue stirring for 3-4 minutes, discharge the materials, and vibrate until slurry appears on the surface of the concrete mixture and there is basically no bubble escaping. Finally, pour and shape it to obtain low-heat early-strength steel fiber mass concrete.
[0008] Furthermore, the mass ratio of the cement, mineral admixture, water, fine aggregate, coarse aggregate and steel fiber is 413:177:147.5:657.3:1050:27.5.
[0009] Furthermore, the cement is silicate cement, with particles of 3-30 μm accounting for more than 90%, and particles smaller than 10 μm accounting for no more than 10%.
[0010] Furthermore, the fine aggregate is medium sand in zone II with a fineness modulus of 2.6-3.0.
[0011] Furthermore, the coarse aggregate is processed from basalt raw rock, with a particle size of 5-20 mm and continuous grading, wherein the needle-like content is not more than 5%, and the crushing value is not more than 8%.
[0012] Furthermore, the steel fiber is an end hook type steel fiber with an aspect ratio of 80, a length of 50 mm, an equivalent diameter of 0.62 mm, and 8037 pieces / kg.
[0013] Furthermore, the pouring temperature into the mold is 15-20°C.
[0014] Furthermore, the mineral admixture is prepared by mixing the following raw materials in parts by weight: 40-60 parts of ground slag, 20-30 parts of fly ash, 14-20 parts of silicon powder and 4-12 parts of water reducing agent.
[0015] Furthermore, the ground slag is not lower than S95 grade.
[0016] Furthermore, the fly ash is Class I or Class II F fly ash.
[0017] Furthermore, the SiO2 content of the silica fume is greater than 90%, and the specific surface area is not less than 15000m 2 / kg.
[0018] The addition of steel fibers can enhance the load-bearing effect of concrete and improve the compressive strength of concrete. The uniform distribution of steel fibers in concrete can prevent the steel fibers from agglomerating, bending or breaking, and can also enhance the fluidity of concrete. The pouring process, through temperature control, not only ensures the rapid hydration of concrete in the early stage to achieve the purpose of increasing early strength, but also helps to reduce the maximum temperature inside the casting structure.
[0019] Furthermore, the water reducing agent is prepared by the following steps:
[0020] S1. In a three-necked flask equipped with a stirring device, triethanolamine, 9-decenoic acid and N,N-dimethylformamide (DMF) were stirred and mixed uniformly, dibutyltin oxide (catalyst) and dicyclohexylcarbodiimide (DCC, dehydrating agent) were added, the reaction temperature was controlled to 75°C, the reaction was kept warm for 8 hours, and stirring was continued during the reaction. After the reaction was completed, part of the solvent was removed by reduced pressure distillation, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:1), and the eluent was removed by rotary evaporation to obtain an intermediate; the ratio of the amount of triethanolamine, 9-decenoic acid, N,N-dimethylformamide, dibutyltin oxide, and dicyclohexylcarbodiimide was 16.3g:16.9g:150mL:0.2g:20.6g;
[0021] Under the catalysis of dibutyltin oxide and dicyclohexylcarbodiimide, the carboxyl group on 9-decenoic acid and the hydroxyl group on triethanolamine undergo esterification reaction. By controlling the molar ratio of the two to be close to 1:1 and the triethanolamine to be slightly excessive, only one hydroxyl group on the triethanolamine participates in the reaction to obtain an intermediate. The specific reaction process is shown below:
[0022]
[0023] S2, in a three-necked flask, add nano-silica, ethanol aqueous solution and hydrochloric acid solution, mix and ultrasonically treat for 30 minutes, then add silane coupling agent KH-570, stir and heat to 60°C, keep warm for 1.5 hours, then stir and heat to 80°C, keep warm for 5 hours, the reaction is completed, cool, filter, wash with acetone, and vacuum dry to obtain modified nano-silica; the ratio of nano-silica, ethanol aqueous solution, hydrochloric acid solution, and silane coupling agent KH-570 is 1g:100mL:10mL:0.6g;
[0024] The surface of nano-silica contains a large number of hydroxyl groups, which can react with the silane coupling agent KH-570 to introduce unsaturated carbon-carbon double bonds on the nano-silica to obtain modified nano-silica;
[0025] S3. In a three-necked flask, ethylene glycol monovinyl polyoxyethylene ether (EPEG), hydrogen peroxide, modified nano-silica, an intermediate and water are mixed to obtain a mixed solution, and then acrylic acid and water are mixed to obtain liquid A; then 3-mercaptopropionic acid, ascorbic acid and water are mixed to obtain liquid B; under stirring, liquid A and liquid B are slowly added to the mixed solution by dropwise addition for 1 hour to carry out free radical polymerization, and the reaction temperature is controlled at 15°C during the dropwise addition. After the dropwise addition is completed, the reaction is continued to be kept warm for 1 hour. After the reaction is completed, the pH value is adjusted to 5-7 with sodium hydroxide aqueous solution to obtain a water reducer; the ratio of ethylene glycol monovinyl polyoxyethylene ether, hydrogen peroxide, modified nano-silica, intermediate, water, acrylic acid, 3-mercaptopropionic acid and ascorbic acid is 30g:5mL:0.3g:1.5g:45mL:3g:0.5g:0.04g;
[0026] Ethylene glycol monovinyl polyoxyethylene ether, modified nano-silica and the intermediate all contain unsaturated carbon-carbon double bonds, and a water reducing agent is obtained by free radical aqueous solution polymerization;
[0027] The prepared water reducer contains nano silicon dioxide, the nano particles have high activity and small particle size, can play the role of dense filling and secondary hydration reinforcement for concrete, enhance the durability of concrete, optimize the physical structure and mechanical properties; by modifying the nano silicon dioxide, grafting different functional groups and molecular structures on its surface, due to the steric hindrance between molecules, the dispersibility of the nano silicon dioxide can be enhanced, so that the performance of the nano silicon dioxide can be fully exerted; in addition, the prepared water reducer is a polycarboxylic acid water reducer, which has good water reducing properties and also has the effects of slow setting and slump retention; in addition, the carboxylic acid functional group can decompose the Ca 2+ produced by the decomposition of ettringite. 2+ and SO4 2- Adsorb free Ca 2+ and SO4 2- The water reducer contains amine groups, which can be used as an early strength agent for concrete, speed up the production cycle, improve work efficiency, and improve the frost resistance of concrete and prevent cracking under low temperature conditions.
[0028] Beneficial effects of the present invention:
[0029] 1. The concrete prepared by the present invention can improve the compressive strength and fluidity of the concrete by uniformly adding steel fibers;
[0030] 2. Through temperature control during pouring, the concrete can be quickly hydrated at an early stage and the temperature inside the pouring structure can be reduced;
[0031] 3. The water reducing agent prepared can greatly improve the strength and durability of concrete by introducing various functional monomers, reduce the cracking of large-volume concrete, and also improve the early strength of concrete and speed up the production cycle;
[0032] Therefore, the concrete prepared by the present invention has high early strength, good crack resistance, low hydration heat, and strong fluidity, and has important application value in the field of building material technology. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Embodiment 1
[0035] Preparation of water reducing agent:
[0036] S1. In a three-necked flask equipped with a stirring device, 16.3 g of triethanolamine, 16.9 g of 9-decenoic acid and 150 mL of N, N-dimethylformamide were stirred and mixed uniformly, 0.2 g of dibutyltin oxide and 20.6 g of dicyclohexylcarbodiimide were added, the reaction temperature was controlled to 75 ° C, and the reaction was kept warm for 8 hours. Stirring was continued during the reaction. After the reaction was completed, part of the solvent was distilled off under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:1), and the eluent was removed by rotary evaporation to obtain an intermediate;
[0037] S2, in a three-necked flask, add 1g of nano-silica (average particle size D50 is 20nm), 100mL of ethanol aqueous solution (mass fraction 90%) and 10mL of hydrochloric acid solution (mass fraction 12%), mix and ultrasonically treat for 30min, then add 0.6g of silane coupling agent KH-570, stir and heat to 60°C, keep warm for 1.5h, then stir and heat to 80°C, keep warm for 5h, the reaction is completed, cool, filter, wash with acetone, and vacuum dry to obtain modified nano-silica;
[0038] S3. In a three-necked flask, 30 g of ethylene glycol monovinyl polyoxyethylene ether (molecular weight 3000), 5 mL of hydrogen peroxide (mass fraction 27.5%), 0.3 g of modified nano-silica, 1.5 g of the intermediate and 15 mL of water were mixed to obtain a mixed solution, and then 3 g of acrylic acid and 15 mL of water were mixed to obtain liquid A; then 0.5 g of 3-mercaptopropionic acid, 0.04 g of ascorbic acid and 15 mL of water were mixed to obtain liquid B; under stirring, liquid A and liquid B were slowly added to the mixed solution by dropwise addition for 1 hour to carry out free radical polymerization. During the dropwise addition, the reaction temperature was controlled at 15°C. After the dropwise addition was completed, the reaction was continued to be kept warm for 1 hour. After the reaction was completed, the pH value was adjusted to 7 with sodium hydroxide aqueous solution to obtain a water reducer.
[0039] Embodiment 2
[0040] Preparation of water reducing agent:
[0041] S1. In a three-necked flask equipped with a stirring device, 32.6 g of triethanolamine, 33.8 g of 9-decenoic acid and 300 mL of N, N-dimethylformamide were stirred and mixed uniformly, 0.4 g of dibutyltin oxide and 41.2 g of dicyclohexylcarbodiimide were added, the reaction temperature was controlled to 75 ° C, and the reaction was kept warm for 8 hours. Stirring was continued during the reaction. After the reaction was completed, part of the solvent was removed by reduced pressure distillation, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:1), and the eluent was removed by rotary evaporation to obtain an intermediate;
[0042] S2, in a three-necked flask, add 2g of nano-silica (average particle size D50 is 20nm), 200mL of ethanol aqueous solution (mass fraction 90%) and 20mL of hydrochloric acid solution (mass fraction 12%), mix and ultrasonically treat for 30min, then add 1.2g of silane coupling agent KH-570, stir and heat to 60°C, keep warm for 1.5h, then stir and heat to 80°C, keep warm for 5h, the reaction is completed, cool, filter, wash with acetone, and vacuum dry to obtain modified nano-silica;
[0043] S3. In a three-necked flask, 60 g of ethylene glycol monovinyl polyoxyethylene ether (molecular weight 3000), 10 mL of hydrogen peroxide (mass fraction 27.5%), 0.6 g of modified nano-silica, 3.0 g of the intermediate and 30 mL of water were mixed to obtain a mixed solution, and then 6 g of acrylic acid and 30 mL of water were mixed to obtain liquid A; then 1.0 g of 3-mercaptopropionic acid, 0.08 g of ascorbic acid and 30 mL of water were mixed to obtain liquid B; under stirring, liquid A and liquid B were slowly added to the mixed solution by dropwise addition for 1 hour to carry out free radical polymerization. During the dropwise addition, the reaction temperature was controlled at 15°C. After the dropwise addition was completed, the reaction was continued to be kept warm for 1 hour. After the reaction was completed, the pH value was adjusted to 7 with sodium hydroxide aqueous solution to obtain a water reducer.
[0044] Embodiment 3
[0045] 413 g of P·O52.5 silicate cement (3-30 μm particles account for more than 90%, less than 10 μm particles do not exceed 10%), 177 g of mineral admixture, 657.3 g of fine aggregate (II zone medium sand with a fineness modulus of 2.6), 1050 g of coarse aggregate (5 mm continuous grading, wherein the needle-like content is not more than 5%, and the crushing value is not more than 8%) and 27.5 g of steel fiber (aspect ratio of 80, length of 50 mm, equivalent diameter of 0.62 mm, 8037 pieces / kg of hook-type steel fiber) are uniformly added into a forced mixer, and the materials are mixed evenly for 10 seconds, and then 147.5 g of water is injected, and the mixing is continued for 3 minutes, and the material is discharged and vibrated until the surface of the concrete mixture is slurried and there is basically no bubble escaping, which is compacted, and finally poured into a mold (the mold temperature is 15° C.) to obtain a low-heat early-strength steel fiber mass concrete;
[0046] The mineral admixtures consist of 40g ground slag (S95 grade), 20g fly ash (grade I or II F), 14g silica fume (silica fume has a SiO2 content of 90% and a specific surface area of 15000m 2 / kg) and 4 g of the water reducing agent prepared in Example 1 were mixed in a mixer.
[0047] Embodiment 4
[0048] 413 g of P·O52.5 silicate cement (3-30 μm particles account for more than 90%, less than 10 μm particles do not exceed 10%), 177 g of mineral admixture, 657.3 g of fine aggregate (II zone medium sand with a fineness modulus of 2.8), 1050 g of coarse aggregate (15 mm continuous grading, wherein the needle-like content is not more than 5%, and the crushing value is not more than 8%) and 27.5 g of steel fiber (aspect ratio of 80, length of 50 mm, equivalent diameter of 0.62 mm, 8037 pieces / kg of hook-type steel fiber) are uniformly added into a forced mixer, and the materials are mixed evenly for 20 seconds, and then 147.5 g of water is injected, and the mixing is continued for 4 minutes, and the material is discharged and vibrated until the surface of the concrete mixture is slurried and there is basically no bubble escaping, which is compacted, and finally poured into a mold (the mold temperature is 20° C.) to obtain a low-heat early-strength steel fiber mass concrete;
[0049] The mineral admixtures consist of 50g ground slag (S95 grade), 25g fly ash (grade I or II F), 17g silica fume (silica fume has a SiO2 content of 90% and a specific surface area of 15000m 2 / kg) and 8 g of the water reducing agent prepared in Example 2 were mixed in a mixer.
[0050] Embodiment 5
[0051] 413 g of P·O52.5 silicate cement (3-30 μm particles account for more than 90%, less than 10 μm particles do not exceed 10%), 177 g of mineral admixture, 657.3 g of fine aggregate (II zone medium sand with a fineness modulus of 3.0), 1050 g of coarse aggregate (20 mm continuous grading, wherein the needle-like content is not more than 5%, and the crushing value is not more than 8%) and 27.5 g of steel fiber (aspect ratio of 80, length of 50 mm, equivalent diameter of 0.62 mm, 8037 pieces / kg of hook-type steel fiber) are uniformly added into a forced mixer, and the materials are mixed evenly for 30 seconds, and then 147.5 g of water is injected, and the mixing is continued for 4 minutes, and the material is discharged and vibrated until the surface of the concrete mixture is slurried and there is basically no bubble escaping, which is compacted, and finally poured into a mold (the mold temperature is 20° C.) to obtain a low-heat early-strength steel fiber mass concrete;
[0052] The mineral admixtures consist of 60g ground slag (S95 grade), 30g fly ash (grade I or II F), 20g silica fume (silica fume has a SiO2 content of 90% and a specific surface area of 15000m 2 / kg) and 12 g of the water reducing agent prepared in Example 1 were mixed in a mixer.
[0053] Comparative Example 1
[0054] A commercially available polycarboxylic acid water reducer of the same quality was used to replace the water reducer in Example 5, and the remaining steps were the same as in Example 5 to prepare concrete.
[0055] Comparative Example 2
[0056] Commercially available concrete was used.
[0057] The concretes obtained in Examples 3, 4, 5 and Comparative Examples 1 and 2 were subjected to the following performance tests:
[0058] The fluidity is determined using the national standard GB / T 8077-2012 "Test method for homogeneity of concrete admixtures";
[0059] The national standard GB / T 50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" was used to measure the compressive strength after 3d and 28d of test curing;
[0060] Use a hydration heat tester to test the hydration heat after 3 days of curing;
[0061] The measured results are shown in the following table:
[0062]
[0063] It can be seen from the above table that the concrete prepared in the embodiment of the present invention has high early strength, low hydration heat, and strong fluidity, and has important application value in the field of building materials technology.
[0064] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0065] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A low-heat early-strength steel fiber mass concrete, which is prepared from cement, mineral admixture, water, fine aggregate, coarse aggregate, and steel fiber in a mass ratio of 413:177:147.5:657.3:1050:27.5, characterized in that: The mineral admixture is prepared by mixing the following raw materials in parts by weight: 40-60 parts of ground slag, 20-30 parts of fly ash, 14-20 parts of silicon powder and 4-12 parts of water reducing agent.
2. The low-heat early-strength steel fiber mass concrete according to claim 1, characterized in that: The water reducing agent is prepared by the following steps: S1. Triethanolamine, 9-decenoic acid and N,N-dimethylformamide were stirred and mixed evenly, dibutyltin oxide and dicyclohexylcarbodiimide were added, and the mixture was reacted at 75° C. for 8 h. Stirring was continued during the reaction. After the reaction was completed, the mixture was distilled under reduced pressure, purified by column chromatography, and rotary evaporated to obtain an intermediate. S2, adding nano-silica, ethanol aqueous solution and hydrochloric acid solution into a three-necked flask, mixing and ultrasonically treating for 30 minutes, adding silane coupling agent KH-570, stirring and heating to 60°C, keeping the temperature for reaction for 1.5 hours, then stirring and heating to 80°C, keeping the temperature for 5 hours, the reaction is completed, cooling, filtering, washing and drying to obtain modified nano-silica; S3. Mix ethylene glycol monovinyl polyoxyethylene ether, hydrogen peroxide, modified nano-silica, an intermediate and water to obtain a mixed solution, then mix acrylic acid and water to obtain liquid A; then mix 3-mercaptopropionic acid, ascorbic acid and water to obtain liquid B; under stirring, add liquid A and liquid B dropwise to the mixed solution for 1 hour. During the addition, control the reaction temperature at 15°C. After the addition is completed, continue to keep the reaction warm for 1 hour. After the reaction is completed, adjust the pH value to 5-7 to obtain a water reducer.
3. The low-heat early-strength steel fiber mass concrete according to claim 2, characterized in that: In step S1, the ratio of triethanolamine, 9-decenoic acid, N,N-dimethylformamide, dibutyltin oxide, and dicyclohexylcarbodiimide is 16.3 g:16.9 g:150 mL:0.2 g:20.6 g.
4. The low-heat early-strength steel fiber mass concrete according to claim 2, characterized in that: In step S2, the ratio of the amount of nano-silica, ethanol aqueous solution, hydrochloric acid solution, and silane coupling agent KH-570 is 1 g: 100 mL: 10 mL: 0.6 g.
5. The low-heat early-strength steel fiber mass concrete according to claim 2, characterized in that: In step S3, the ratio of ethylene glycol monovinyl polyoxyethylene ether, hydrogen peroxide, modified nano-silica, intermediate, water, acrylic acid, 3-mercaptopropionic acid and ascorbic acid is 30g:5mL:0.3g:1.5g:45mL:3g:0.5g:0.04g.
6. The low-heat early-strength steel fiber mass concrete according to claim 1, characterized in that: The cement is silicate cement, with particles of 3-30 μm accounting for more than 90%, and particles smaller than 10 μm not exceeding 10%.
7. The low-heat early-strength steel fiber mass concrete according to claim 1, characterized in that: The fine aggregate is medium sand in zone II with a fineness modulus of 2.6-3.
0.
8. The low-heat early-strength steel fiber mass concrete according to claim 1, characterized in that: The coarse aggregate is processed from basalt raw rock, with a particle size of 5-20 mm and continuous grading, wherein the needle-like content is not more than 5%, and the crushing value is not more than 8%.
9. The low-heat early-strength steel fiber mass concrete according to claim 1, characterized in that: The steel fiber is an end hook type steel fiber with an aspect ratio of 80, a length of 50 mm, an equivalent diameter of 0.62 mm, and 8037 pieces / kg.
10. The process for preparing low-heat early-strength steel fiber mass concrete according to claim 1, characterized in that: The following steps are involved: Evenly add cement, mineral admixture, fine aggregate, coarse aggregate and steel fiber into a forced mixer, stir to make the materials evenly mixed, then inject water, continue stirring, discharge the materials, vibrate until compacted, and finally pour into shape to obtain low-heat early-strength steel fiber mass concrete.
Citation Information
Patent Citations
Production process of early-strength alkali-free accelerating agent and product obtained with production process
CN106830803A
Steel slag doped premixed concrete and preparation method thereof
CN111792883A
Shrinkage reducing agent for ultra-high performance concrete and preparation method of shrinkage reducing agent
CN112830704A
Fiber composite maritime work cement-based material and preparation method thereof
CN118344102A
Organic-inorganic hybrid flame-retardant foam composition and composite building material produced therefrom
JP1996176259A